Sosialisasi Inovasi dan Pemanfaatan Limbah Pertanian Berupa Pupuk Jakaba dan Keripik Gedebog Pisang kepada Petani Desa Balongwono Kecamatan Trowulan Kabupaten Mojokerto - Lailatus Sa'adah; Mohammad Yusuf Habibi; Imam Achmad Ahadin; Jafar Sodiq Maksum; Rizki Wulandari; Muhammad Andhika Budi Prasetyo; Siti Nur Qomariyah (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This community service program in Balongwono Village, Trowulan District, Mojokerto Regency aimed to enhance farmers’ awareness and understanding of agricultural waste utilization and innovation through the introduction of Jakaba liquid organic fertilizer and banana pseudo-stem (gedebog) chips. Jakaba, produced from the fermentation of rice-washing water, has been proven to improve soil fertility, accelerate plant growth, and reduce dependence on chemical fertilizers, while banana pseudo-stem chips provide an economically valuable product from agricultural waste that is often underutilized. The program was conducted through face-to-face socialization, interactive discussions, and the distribution of product samples to farmers. The results indicated a significant improvement in farmers’ knowledge, as shown by the increase in average scores from 79.54 (pre-test) to 90.28 (post-test). Therefore, this program effectively supports sustainable agriculture, creates value-added products from waste, and contributes to improving the welfare of rural communities.